Nurses' preparedness for infectious disease outbreaks: A literature review and narrative synthesis of qualitative evidence. Issue 7 (11th January 2018) - Lam, Stanley K. K.; Kwong, Enid W. Y.; Hung, Maria S. Y.; Pang, Samantha M. C.; Chiang, Vico C. L.
Abstract : Aims and objectives: To explore the core components that constitute nurses' preparedness in an epidemic event. Background: Healthcare service providers have worked to augment efforts to protect the public from the impact of epidemic events. While constituting the major healthcare taskforce, nurses are frequently tasked with fronting the response to an infectious disease outbreak. Given the crucial role of nurses in the management of prevailing epidemics, the constituents of their preparedness in epidemic events should be identified. Design: A systematic search was undertaken to identify eligible studies from the literature. A narrative synthesis approach was employed to extract and synthesise findings of the reviewed qualitative studies. Methods: Seven qualitative studies on nurses' experience and perceptions of epidemic events were examined for scientific quality using the Critical Appraisal Skills Programme Qualitative Checklist. Findings of these studies were synthesised adopting a narrative synthesis approach. Results: Three interplaying themes were identified as follows: (i) personal resources, (ii) workplace resources and (iii) situational influences. The findings suggest that an effective epidemic outbreak response would require further effort to reinforce the interplay between individual nurses, healthcare institutions and the governments. Conclusions: The practical interplay among individual nurses, healthcare institutions and the governments is crucial in establishing an effective epidemic response. Further research on the understanding of the dynamic process of preparedness development is recommended to set future directions in research. Relevance to clinical practice: This study offers important insights for devising future strategies in enhancing nurses' preparedness and response to an epidemic event. These include recommendations on providing education and training to nurses regarding infectious diseases, fostering institutional assistance and support in an outbreak and revising government policies and planning.